2018
DOI: 10.1155/2018/9601801
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Beta Cell Death: Novel Potential Mechanisms in Diabetes Therapy

Abstract: Purpose of ReviewDescribing the diverse molecular mechanisms (particularly immunological) involved in the death of the pancreatic beta cell in type 1 and type 2 diabetes mellitus. Recent FindingsBeta cell death is the final event in a series of mechanisms that, up to date, have not been entirely clarified; it represents the pathophysiological mechanism in the natural history of diabetes mellitus. These mechanisms are not limited to an apoptotic process only, which is characteristic of the immune-mediated insul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(103 citation statements)
references
References 186 publications
2
98
0
3
Order By: Relevance
“…In line with the previous findings [11], we also found that there are distinct transcriptome profiles between LADA and T1D and T2D. In T1D, β-cell destruction is thought to be largely mediated by autoreactive T cells and autoantibody-induced autoimmune attack [12,13]. The presence of autoimmune antibodies against β-cells is one of the diagnostic criteria of LADA, suggesting that the immune-mediated β-cell death also plays pivotal roles in the pathogenesis of LADA.…”
Section: Discussionsupporting
confidence: 91%
“…In line with the previous findings [11], we also found that there are distinct transcriptome profiles between LADA and T1D and T2D. In T1D, β-cell destruction is thought to be largely mediated by autoreactive T cells and autoantibody-induced autoimmune attack [12,13]. The presence of autoimmune antibodies against β-cells is one of the diagnostic criteria of LADA, suggesting that the immune-mediated β-cell death also plays pivotal roles in the pathogenesis of LADA.…”
Section: Discussionsupporting
confidence: 91%
“…In diabetics, β‐cells secrete larger‐than‐normal amounts of insulin to overcome insulin resistance, causing overwork and overproduction of insulin for extended periods of time. Glucolipotoxicity also damages β‐cells, leading to little or no insulin production in a vicious cycle that ultimately promotes cell dysfunction and death . Thus, glucolipotoxicity‐mediated β‐cell loss is a critical causal factor of the late stages of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…While apoptosis is considered as a primary regulated cell death pathway, recent studies have identified several other pathways of regulated cell deaths, including apoptosis, necroptosis, ferroptosis, pyroptosis, and parthanatos . Necroptosis is a form of regulated necrosis that has recently been suggested to be a major pathway of islet cell death in the development of diabetes and during both in vitro culture and islet transplantation . The inflammatory cascade triggered by the release of danger‐associated molecular patterns (DAMPs), such as high‐mobility group box 1 (HMGB1) and DNA fragments, after islet necroptosis furtherly contributes to islet damage, reduced islet survival, enhanced immune responses after implantation, and consequently impaired outcomes of islet transplantation in both mice and humans …”
Section: Introductionmentioning
confidence: 99%